Une doctrine d'abus de procédure revigorée en droit pénal canadien - Grondin, Rachel (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 1983)
This article examines the doctrine of abuse of process in Canadian criminal law in the light of two recent events, the decision of the Supreme Court of Canada in Amato c. R. and the adoption of the Canadian Charter of Rights and Freedoms. The consideration of Amato v. R. in the firts part of the article shows that the majority of judges of the Supreme Court support the existence of the doctrine of abuse of law, and their reasons for this are examined. The effects of the Charter upon such a doctrine is demonstrated in the second part. The American experience is cited, showing the interrelationship of the U.S. Constitution and the doctrine of abuse of process. This is followed by a comparative table of Canadian cases in which the procedure was halted either because of the doctrine or by virtue of the Charter, particularly s. 24(1) which permits judges to stay proceedings for reasons of infringement or denial of guaranteed rights or freedoms. The article concludes that the doctrine has not been superceded by the Charter, but rather that it plays an important role par ailed to it : the former protects the integrity of the legal process while the latter safeguards the rights of the individual.